Trend 2003 - 2009. Institute of Museum and Library Services. Public Libraries Survey: Current Electronic Serial Subscriptions | Country: USA | State: Alaska | County: Prince Wales Ketchikan | Libraries: METLAKATLA CENTENNIAL LIBRARY, 2003-2009. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 058-001-037. - Institute Of Museum And Library Services (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Institute of Museum and Library Services (2015). Public Libraries Survey: Current Electronic Serial Subscriptions | Country: USA | State: Alaska | County: Prince Wales Ketchikan | Libraries: METLAKATLA CENTENNIAL LIBRARY, 2003-2009. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 058-001-037. Dataset: The number of subscriptions to electronic serial publications within a library system. Examples include periodicals (magazines), newspapers, annuals, some government documents, some reference tools, and numbered monographic series. Excluded are indexing and abstracting databases that include full-text serial content (eg, EBSCOhost, ProQuest, OCLC FirstSearch). This dataset contains data on the resources, finances, and use of the public libraries in the United States presented by fiscal year. Data are collected in an annual survey of over 9,000 public libraries conducted by the Institute of Museum and Library Services. Each public library provided data for a 12-month period covering the fiscal year as defined by the locale. Please note that the National Center for Education Statistics (NCES) conducted the FY2005 and earlier Public Libraries Surveys and produced the data files. Category: Education Source: Institute of Museum and Library Services The Institute of Museum and Library Services provides federal funds to libraries and museums in the United States to support improvements in technology and public services. The Institute was founded in 1996 as authorized under the Museum and Library Services Act. http://www.imls.gov/ Subject: Expenditures, Public Libraries